New forage variety Avena sativa AV25T, “Altoandina” to improve the efficiency of dairy farming systems in the Colombian high tropics - CGIAR Research Program on Livestock (2020)
Variety was released in 2020 and currently, seed multiplication takes place with an international seed provider